Physician Confidence in Dental Trauma Treatment and the Introduction of a Dental Trauma Decision-Making Pathway for the Pediatric Emergency Department. Issue 11 (November 2019) - Cully, Matthew; Cully, Jennifer; Nietert, Paul J.; Titus, M. Olivia
Abstract : Objectives: The objectives of this study were to (1) survey and report the awareness and confidence of pediatric emergency medicine physicians in the management of dental trauma and (2) determine the prevalence of dental trauma decision-making pathway utilization in the pediatric emergency department. Methods: A survey was distributed through e-mail to the pediatric emergency medicine discussion list via Brown University LISTSERV. The survey study included 10 questions and was multiple-choice. The survey contained questions about physician confidence and their use of a dental trauma decision-making pathway. Results: A total of 285 individuals responded to the survey. Somewhat confident was the most common response (61%) followed by not confident (20%) and confident (19%) by respondents in treating dental trauma. Forty-one percent of respondents felt comfortable, 39% somewhat comfortable, 19% not comfortable, and 1% not sure in replanting an avulsed tooth. Only 6% of respondents reported that their pediatric emergency department always or sometimes uses a dental trauma decision-making pathway, whereas 78% of pediatric emergency departments do not. Conclusions: We believe that the adoption of a decision-making pathway will provide timely management, improve emergency physician comfort, and enhance outcomes for pediatric patients presenting with a dental trauma. A future multicenter review will aim to evaluate these goals based on the utilization of our dental trauma decision-making pathway. Abstract : Supplemental digital content is available in the text.